Rancang Bangun Kompor Berbahan Bakar Limbah Oli dengan Sistem Pemantik Elektrik - Saputra, Muhamad Veri Dwi; Nurhadi, Nurhadi; Darmo, Adityo Noor Setyo Hadi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Used oil is a hazardous waste that may cause environmental pollution if not properly managed. One alternative utilization is its use as fuel for stoves. This study aims to design and develop a used-oil-fueled stove equipped with an electric ignition system and to investigate the effect of blower speed variations on combustion temperature. The research method consisted of stove fabrication, functional testing, and combustion temperature measurements at various blower speeds. The stove was composed of a frame, combustion chamber, nozzle, oil tank, flow system, centrifugal blower, and electric igniter. The results indicate that the stove operated properly and that the electric igniter effectively accelerated the initial ignition process. An increase in blower speed resulted in higher combustion temperatures, with a maximum temperature of 447.9 °C achieved at the highest blower speed. The developed stove demonstrates potential as an alternative technology for utilizing used oil as fuel in small-scale industrial applications.